Uterine compression suture in uterine atony during cesarean section - PACORA, PERCY (2004)
Objetive: To ascertain whether the use of uterine compression suture (B-Lynch technique) during a cesarean section with uterine atony decreases the amount of blood loss and prevents postpartum hysterectomy. Material and Methods: Retrospective study of all the cesarean section deliveries complicated by uterine atony from January 1, 1990 through December 31, 2003 at San Bartolome Hospital in Lima. The standard management of uterine atony included uterine massage, use of uterotonic agents (ocytocin, prostaglandins), uterine/hypogastric artery ligature and, finally, postpartum hysterectomy. Maternal and Infant clinical charts were reviewed and variables were entered into a computer system analysis (SPSS version 10). Results: Forty six cases were identified: B-Lynch technique was used in 30 cases and the standard method in 16 cases. There was no difference in maternal characteristic between both groups. B-Lynch technique group presented subjective lower amount of blood loss, received lower units of blood transfusion and had significant lower risk of postpartum hysterectomy as compared to the standard method group (mean ± SD: 1144,4±311,7 mL vs 1666,9±794,4 mL, p<0,05; 0,36±0,66 vs 2,90±3,64, p<0,05; and OR 0,08, CI95% 0,01-0,45, p<0,01, respectively). Conclusions: Uterine compression sutures during a cesarean section with uterine atony may reduce the amount of blood loss, the number of blood transfusions and the use of hysterectomy as compared to the standard method.